Pengaruh Struktur Modal, Arus Kas Operasi, dan Pertumbuhan Laba terhadap Kualitas Laba - Engelina Jismaneri; Indawati Indawati (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study examined the effect of Capital Structure, Operating Cash Flow, and Profit Growth on Earnings Quality. The study focused on companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. A purposive sampling technique was applied, selecting 30 companies from the population of 125 based on specific criteria, which were then analyzed over five years of observation, resulting in 150 observation units. The data were quantitative, sourced from the companies’ annual financial reports, and analyzed using Eviews 12 software. Panel data regression was used to analyze the data. The findings of this study indicate that Capital Structure, Operating Cash Flow, and Profit Growth together influence Earnings Quality. More specifically, Capital Structure was found to have a partial effect on Earnings Quality. Operating Cash Flow showed a significant linear relationship with Earnings Quality, indicating its substantial impact. However, Profit Growth was not found to affect Earnings Quality. This study highlights the importance of capital structure and operating cash flow in influencing earnings quality and provides insights for investors and financial analysts in evaluating the financial health of companies within the consumer non-cyclicals sector. Further studies are suggested to explore the role of other financial factors in determining earnings quality.